Genetic ablation of β-catenin inhibits the proliferative phenotype of mouse liver adenomas - Singh, Y (Nature Publishing Group, 2014)
BACKGROUND: Aberrant activation of Wnt/β-catenin has been implicated in various cancer-related processes, for example, proliferation or tumour cell survival. However, the exact mechanism by which β-catenin provides liver tumour cells with a selective advantage is still unclear. This study was aimed to analyse growth behaviour and survival of β-catenin-driven mouse liver tumours after β-catenin ablation. METHODS: Transgenic mice with a controllable hepatocyte-specific knockout of Ctnnb1 (encoding β-catenin) were generated and liver tumours were induced by means of a N-nitrosodiethylamine/phenobarbital tumour initiation/promotion protocol, which leads to the outgrowth of hepatocellular tumours with activated β-catenin. Cre recombinase was activated and the effects of the knockout in the tumours were studied. RESULTS: Activation of Cre recombinase led to the knockout of Ctnnb1 in a fraction of tumour cells, thus resulting in the formation of two different tumour cell subpopulations, with or without β-catenin. Comparative analysis of the two subpopulations revealed that cell proliferation was significantly decreased in Ctnnb1-deleted hepatoma cells, compared with the corresponding non-deleted cell population, whereas no increased rate of apoptosis after knockout of Ctnnb1 was observed. CONCLUSIONS: β-catenin-dependent signalling is an important regulator of hepatoma cell growth in mice, but not a crucial factor in the regulation of tumour survival.